ANALISIS YURIDIS TERHADAP EKSEKUSI DALAM PERJANJIAN JAMINAN FIDUSIA YANG TIDAK DIDAFTARKAN (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 97K/PDT/2015) - CHRISTINA NORIS TARIGAN (PREMISE LAW JURNAL, 2017)
Fiduciary contract is a loan agreement from a creditor to a debtor which involves collateral controlled by its owner. The result of the research showed that unregistered fiduciary contract was not valid because it is between person and another person, while there was noreal property right in it, so that the characters of the object such as droit de suite and droit de preference are not bound in the creditor as the giver of fiduciary collateral. Execution on unregistered fiduciary collateral cannot be done directly since there is no executorial title that has the same evidence as the Court’s Ruling which is final and conclusive. In this case, the pattern looked like fiduciary, but it was not registered so that the judge’s consideration was not fair for the plaintiff as the receiver of fiduciary. Therefore, this act violates Article 11 of UUJF in which an object which is burdened with fiduciary collateral has to be registered.Keywords: Execution, Registration, Fiduciary Collateral